Analisis Motivasi Belajar Siswa terhadap Pembelajaran Daring PJOK Selama Pandemi Coronavirus Disease (Covid-19) di MAN 1 Lamongan - Taufiq, A.; Eka Arisandi, Rendis (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2025)
The purpose of this study is to analyze students' learning motivation in PJOK learning at MAN Lamongan. With a descriptive qualitative approach method to find facts in the field and descriptive analysis and also inferential analysis, this research is also included in ex post facto research where this research is carried out after what is researched has happened. The results of this study taken from 243 questionnaires that were distributed showed that high motivation to get good grades is the main motivation in participating in online learning so that by increasing student learning motivation there is a significant increase in the value and learning goals themselves. By providing motivation during online learning, students will avoid boredom and boredom. Student learning motivation in PJOK online learning is able to encourage the learning process of students from outside or inside in PJOK online learning at MAN Lamongan.